Recovery of Consciousness and Functional Outcome in Moderate and Severe Traumatic Brain Injury - Kowalski, Robert G; Hammond, Flora M; Weintraub, Alan H; Nakase-Richardson, Risa; Zafonte, Ross D; Whyte, John; Giacino, Joseph T (JAMA neurology, 2021)
Traumatic brain injury (TBI) leads to 2.9 million visits to US emergency departments annually and frequently involves a disorder of consciousness (DOC). Early treatment, including withdrawal of life-sustaining therapies and rehabilitation, is often predicated on the assumed worse outcome of disrupted consciousness. To quantify the loss of consciousness, factors associated with recovery, and return to functional independence in a 31-year sample of patients with moderate or severe brain trauma. This cohort study analyzed patients with TBI who were enrolled in the Traumatic Brain Injury Model Systems National Database, a prospective, multiyear, longitudinal database. Patients were survivors of moderate or severe TBI who were discharged from acute hospitalization and admitted to inpatient rehabilitation from January 4, 1989, to June 19, 2019, at 1 of 23 inpatient rehabilitation centers that participated in the Traumatic Brain Injury Model Systems program. Follow-up for the study was through completion of inpatient rehabilitation. Traumatic brain injury. Outcome measures were Glasgow Coma Scale in the emergency department, Disability Rating Scale, posttraumatic amnesia, and Functional Independence Measure. Patient-related data included demographic characteristics, injury cause, and brain computed tomography findings. The 17 470 patients with TBI analyzed in this study had a median (interquartile range [IQR]) age at injury of 39 (25-56) years and included 12 854 male individuals (74%). Of these patients, 7547 (57%) experienced initial loss of consciousness, which persisted to rehabilitation in 2058 patients (12%). Those with persisting DOC were younger; had more high-velocity injuries; had intracranial mass effect, intraventricular hemorrhage, and subcortical contusion; and had longer acute care than patients without DOC. Eighty-two percent (n = 1674) of comatose patients recovered consciousness during inpatient rehabilitation. In a multivariable analysis, the factors associated with consciousness recovery were absence of intraventricular hemorrhage (adjusted odds ratio [OR], 0.678; 95% CI, 0.532-0.863; P = .002) and intracranial mass effect (adjusted OR, 0.759; 95% CI, 0.595-0.968; P = .03). Functional improvement (change in total functional independence score from admission to discharge) was +43 for patients with DOC and +37 for those without DOC (P = .002), and 803 of 2013 patients with DOC (40%) became partially or fully independent. Younger age, male sex, and absence of intraventricular hemorrhage, intracranial mass effect, and subcortical contusion were associated with better functional outcome. Findings were consistent across the 3 decades of the database. This study found that DOC occurred initially in most patients with TBI and persisted in some patients after rehabilitation, but most patients with persisting DOC recovered consciousness during rehabilitation. This recovery trajectory may inform acute and rehabilitation treatment decisions and suggests caution is warranted in consideration of withdrawing or withholding care in patients with TBI and DOC.